1990
DOI: 10.1038/bjc.1990.118
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H nitroblue tetrazolium reductase levels in apparently normoxic tissues: a histochemical study correlating enzyme activity with binding of radiolabelled misonidazole

Abstract: Hack and Helmy's method for the histochemical identification of NAD(P)H nitroblue tetrazolium reductase activity was employed to pinpoint reductase activity in certain cells in the mouse. High activity was observed in the following: lower airway epithelium, liver (centrilobular zone), eyelid (meibomian and sebaceous glands), vulval gland and parotid gland (striated cells of intralobular ducts). All of these cells had previously been identified as sites of binding of the reactive metabolites formed from the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…Recently Maxwell et al (1989a,b) and previously Van OsCorby et al (1987) have pointed to low oxygen tension being the likely cause of this retention for MISO. While this may be so there is also a higher reductase level in zone 3 which might contribute significantly to the localisation of all three drugs (Pette & Brandau, 1966;Cobb et al, 1990a The ARG grain localisation in part reflected the whole tissue measurements and supported the observation that some nitroimidazoles are able to form reactive, binding, metabolites in probably normoxic tissues with high reductase levels. It is by no means clear whether the high grain density can be regarded as a measure of cytotoxic potential in tissues.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Recently Maxwell et al (1989a,b) and previously Van OsCorby et al (1987) have pointed to low oxygen tension being the likely cause of this retention for MISO. While this may be so there is also a higher reductase level in zone 3 which might contribute significantly to the localisation of all three drugs (Pette & Brandau, 1966;Cobb et al, 1990a The ARG grain localisation in part reflected the whole tissue measurements and supported the observation that some nitroimidazoles are able to form reactive, binding, metabolites in probably normoxic tissues with high reductase levels. It is by no means clear whether the high grain density can be regarded as a measure of cytotoxic potential in tissues.…”
Section: Discussionmentioning
confidence: 63%
“…This concept is supported by the close correlation of high tritium retention with high grain count in the target tissues: sebaceous gland group, stratified squamous epithelium (oesophagus) and liver. In a recent publication on MISO we have pointed out that these tissues have in common high levels of reductase and we have suggested that, despite the likely presence of significant amounts of oxygen, nitroimidazoles are reduced to reactive, binding, metabolite(s) in these tissues (Cobb et al, 1990a). The same may well apply to PIMO and RSU 1069.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been reported that human gliomas contain bioreductive enzymes [NAD(P)H-cytochrome P450 oxidoreductase, NAD(P)H -quinone oxidoreductase] (Rampling et al, 1994), which might be involved in the reductive activation of nitroimidazoles (Cobb et al, 1990;Parliament et al, 1992;Joseph et al, 1994). Thus, the finding that unresected, untreated human malignant gliomas failed to show avidity for the hypoxia marker ['231]IAZA in situ was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Garrecht and Chapman (1983) noted the presence of significant '4C-misonidazole binding to murine liver, nasal and oral mucosa, as well as to implanted EMT6 tumours growing in BALB/c mice. Detailed studies using both scintillation counting and autoradiography have shown significant retention of misonidazole in many different murine tissues, including oesophagus, airway epithelium, liver, foot pad, eyelid (meibomian gland), sebaceous glands, stomach, and parotid gland (Akel et al, 1986, Cobb et al, 1989, 1990aMacManus et al, 1989). It could be argued that at least one of these tissues, liver, contains hypoxic cells (Van OsCorby & Chapman, 1986Maxwell et al, 1989;MacManus et al, 1989).…”
mentioning
confidence: 99%